2019
DOI: 10.31357/vjm.v5i1.3914
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Leader-Member Relationship on Introverted and Extroverted Personality Traits of Leaders and Organizational Citizenship Behavior of Followers: An Empirical Study of IT Industry in Sri Lanka

Abstract: This study focuses on investigating the relationship between personality and leadership supports the claim that individual differences may be the predictors of leadership effectiveness in contemporary organizations. Extended studies stress that ‘Big-Five ‘personality dimensions are related to leadership criteria and further identified introversion-extroversion as a key element of an individual personality. In general, the main differences between effective and less effective leaders are that, effective leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…According to Andrade (2022), women may perceive themselves as possessing lower levels of competence in leadership positions when leadership is closely linked with predominantly masculine attributes. Moreover, it has been observed that the leader-member relationship and organizational citizenship behavior of followers can be impacted by the introverted and extroverted personality traits exhibited by leaders (Niranga & Dharmadasa, 2019). According to Niranga and Dharmadasa (2019), leader personality traits play a crucial role in elucidating a substantial proportion of the variability observed in leadership effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Andrade (2022), women may perceive themselves as possessing lower levels of competence in leadership positions when leadership is closely linked with predominantly masculine attributes. Moreover, it has been observed that the leader-member relationship and organizational citizenship behavior of followers can be impacted by the introverted and extroverted personality traits exhibited by leaders (Niranga & Dharmadasa, 2019). According to Niranga and Dharmadasa (2019), leader personality traits play a crucial role in elucidating a substantial proportion of the variability observed in leadership effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, it has been observed that the leader-member relationship and organizational citizenship behavior of followers can be impacted by the introverted and extroverted personality traits exhibited by leaders (Niranga & Dharmadasa, 2019). According to Niranga and Dharmadasa (2019), leader personality traits play a crucial role in elucidating a substantial proportion of the variability observed in leadership effectiveness. In summary, personality traits have a significant impact on the effectiveness of leadership, as certain traits are closely linked to both the emergence and effectiveness of leaders (Gkintoni & Dimakos, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others, for example, Nugraha (2021), Asgari, Mezgineiad and Taherpour (2020), Saira, Mansoor, Ali (2021), Nasar and Arar (2019),Dartey-Baah, K., & Addo, S. A. ( 2019), Arar and Abu Nasar (2019), Niranga and Dharmadasa(2019), Lian andTui (2012),Nurjanah, pebianti andHandaru(2020) analyzed the relationship between leadership styles and OCB with the intervening variables.…”
Section: The Relationship Between Leadership Style (Transformational ...mentioning
confidence: 99%